Gambogic acid sensitizes breast cancer cells to TRAIL-induced apoptosis by promoting the crosstalk of extrinsic and intrinsic apoptotic signalings. (September 2018) - Wang, Shengpeng; Xu, Yingqi; Li, Chenyang; Tao, Hongxun; Wang, Anqi; Sun, Chenyu; Zhong, Zhangfeng; Wu, Xu; Li, Peng; Wang, Yitao
Abstract: Due to the ability of tumor necrosis factor (TNF)-related apoptosis-inducing ligand (TRAIL) to induce cancer cell apoptosis selectively, TRAIL has attracted significant interest in the treatment of cancer. However, although TRAIL triggers apoptosis in a broad range of cancer cells, most primary cancers are often intrinsically TRAIL-resistant, or can acquire resistance after TRAIL treatment, evocating new strategies to overcome TRAIL resistance. Gambogic acid (GA), an active constituent of Garcinia Hanburyi (Teng Huang in Chinese), has been applied for thousands of years for medicinal uses, however, the potential effect of GA in combating cancer resistance remains poorly investigated. In this study, we found that GA could increase the sensitivity of breast cancer cells to TRAIL and enhance TRAIL-induced apoptosis. GA cooperated with TRAIL to decrease the levels of anti-apoptotic proteins and activate Bid (BH3 interacting-domain death agonist) to promote the crosstalk of extrinsic and intrinsic apoptotic signaling, rather than increasing the expression of TRAIL receptors DR4 and DR5. These findings may open a new window in the treatment of breast cancer using TRAIL in combination with GA.